(untitled) (CIPEEX, 2025)
This work analyzes the technological and commercial challenges faced by Vale S.A., one of the largest mining companies in the world, with a focus on its commodity export operations. The research explores the company’s trajectory since its founding, addressing its import and export patterns, commercial strategies, and challenges in the international market. Additionally, it discusses value addition in the steel production chain and the sustainability challenges faced by the Brazilian mining industry. The study also examines Vale’s corporate social responsibility initiatives and the use of environmental soft power to enhance its global reputation.